Cervical Cancer Screening Program in Bangladesh (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Cervical cancer (CC) is the fourth most common cancer in women worldwidewith an estimated 569,847 new cases and 311,365 deaths in the year 2018. In Bangladesh,the incidence of CC was 8068 and 5214 women died from CC in the year 2018.1CC constitutesabout 12% of the female cancer in this country.1Methods: The present situation of cervical cancer screening program is reviewed.Results: The Government of Bangladesh (GOB) adopted visual inspection of cervix withacetic acid (VIA) method for cervical cancer screening. The major strengths of VIA is itssimplicity, low cost, potential for immediate linkage with investigations/treatment, feasible inlow resource settings and the possibility of rapid training to the providers. The GOB hasextended the program to all districts and selected upazilas.The screening programme hasbeen implemented through capacity building of service providers of Medical College Hospitals(MCHs), District Hospitals (DHs), Mother and Child care Welfare Centers (MCWCs) andselected Upazila Health Compleses(UHCs) and several institutes.Serviceprovidersareperforming VIA for the women of 30 years and above at about 417 VIA centres at primary,secondary and tertiary level health care facilities of 64 districts of Bangladesh. Screen positivecases are being referred to the colposcopy clinics of 14 government MCHs and BSMMU,where evaluation and management are carried out. From January 2005 to June 2017,1647380VIA tests were performed at different facilities with 4.6%positivity.Among the VIA+ve women attending women at the colposcopy clinic of Bangabandhu Sheikh Mujib MedicalUniversity (BSMMU), 51% had precancerous or cancerous condition of the cervix, 3312(14.10%) were treated by local excision, 2428 (10.30%)by local ablative method and1413(6%) women with cervical cancer were referred to oncology. In Bangladesh, LEEPand thermalablation has acquired acceptability as a commonly used treatment method for selected CINand ‘see-and-treat’ approach for high grade diseases combining colposcopy and LEEP/thermal ablation has been adopted since the year 2010 to improve compliance to treatment.Conclusion: Bangladesh has established VIA as screening test for prevention of cervicalcancer in quiet a good number of facilities with wide coverage. But the program has to beexpanded readily to prevent cancer and reduce sufferings & untimely death of women dueto this devastating disease.Bangladesh J Obstet Gynaecol, 2018; Vol. 33(1) : 63-73